AB0465 Comparison of Abatacept Efficacy and Safety in Different Stages Rheumatoid Arthritis. (9th June 2015) - Maria, K.A.; Lukina, G.V.; Sigidin, Y.A.; Aronova, E.S.; Glukhova, S.I.; Luchihina, E.L.; Karateev, D.E.; Nasonov, E.L.
Abstract : Background: Although Abatacept (ABA) is widely used in treatment of RA. there isn't enough data about its effectiveness in patients with early (ERA) and long-standing (LS) rheumatoid arthritis. Objectives: To compare effect of ABA in patients (pts) with different stages of rheumatoid arthritis (RA). Methods: Patients (n=80) with active RA and an inadequate response to synthetic DMARDs or biologics (adalimumab, rituximab, tocilizumab) were divided in two groups, patients with less than three years duration (ERA) and more than three years duration (LS RA) of RA. Pts with early RA and LS RA were 51% and 49%, respectively. Most of them were women, age 49±13 years, with a high disease activity (DAS28=5, 28±1, 1), RF-positive (75, 7%) and ACPA-positive (75%). Infusions of abatacept (10 mg/kg) were provided three times every 2 weeks followed by every 4 weeks. Disease activity was assessed by DAS28. Results were assessed every 12 weeks according to EULAR criteria. Results: Initially patients with early RA has DAS28 5, 26±0, 89, with long-standing RA - 5, 3±1, 3. ABA decrease activity of RA in both groups, after 3 months of therapy good and moderate response by EULAR criteria was achieved in 82.2% in the group of ERA and in 67.5% of patients with LS RA (p<0.05). There was no significant difference in achieving good EULAR response between two groups after 3 months (26, 47% - ERA; 25, 7% - LS RA) and 6 months of therapy (31, 9% - ERA; 35, 2% - LS RA). However, the number of non-responders to the therapy in pts with LS RA was significantly higher both after 3 months and 6 months (32, 35% and 25, 3%) as compared to pts with ERA (17.6% and 17.02% respectively). There were registered 25 adverse events (AE) in 19 (23%) pts. The most frequent AE were upper respiratory tract infections - 8 pts. One pt has herpes zoster and one, abscess of the right thumb. Conclusions: Abatacept has shown significant clinical benefit in patients who had an inadequate response to previous therapy. There was no significant difference in achieving good EULAR response between pts with early and LS RA. There were more patients with an inadequate response to ABA in the LS RA group. ABA was well tolerated, AE were registered only in 23% of patients. ABA is an effective drug with a good safety profile in the treatment of both LS and ERA. Disclosure of Interest: None declared